THE LEARNING STYLES OF MILLENNIAL GENERATION IN UNIVERSITY: A STUDY IN INDONESIAN CONTEXT - Djiwandono, Patrisius Istiarto (UPI Press, 2017)
The paper reports a study of the learning styles of Millennial Generation. It aims to identify their learning styles, determine the correlations between their learning styles and their achievements in language skill courses and in a content course, and determine the relationship between the amount of their verbal report of learning styles and their achievement in the content course. A group of 22 learners described how they manage their learning of a content subject. Their written answers were coded to find their preferred styles in learning the subject. The coding generated a common profile of their learning styles, most of which differ considerably from the common characteristics of Millennial Generation in the literature. No significant correlation is evident between their learning styles and their achievements in language and content course. Finally, there is a modest correlation between the amount of verbal report and their ultimate mastery of the content course. The instructional context and cultural aspects are thought to have shaped the respondents’ learning styles.Keywords: Millennial Generation, learning styles, cultural influence